Uso de preposiciones en niños de 5 y 6 años institucionalizados y no institucionalizados de la ciudad de Cusco - Santos Salcedo, Gladys Almendra (2024)
The purpose of this research was to determine if there is a difference in the frequency of preposition use between institutionalized and non-institutionalized 5 and 6 year old children in the city of Cusco. It was also considered important to know the difference between the errors made when using prepositions and the performance obtained when completing sentences with these prepositions. The type of research was substantive descriptive and the comparative descriptive design, the sample consisted of 75 children between 5 and 6 years of age, 54 were non-institutionalized children (25 children belonging to a private initial educational institution and 29 children belonging to a state initial educational institution) and 21 institutionalized children belonging to a Residential Reception Center (CAR). Likewise, two assessment instruments were used, the analysis of the language sample (mean utterance length) and the morphosyntax task of the Clinical Assessment of Language Fundamentals Celf-5. The conclusion reached by the present research confirms a significant difference in the frequency of preposition use between institutionalized and non-institutionalized children, showing a higher frequency of preposition use in non-institutionalized children.